Genetic association of TLR4 Asp299Gly, TLR4 Thr399Ile, and CD14 C‐159T polymorphisms with the risk of severe RSV infection: a meta‐analysis. Issue 3 (7th March 2016) - Zhou, Jiahui; Zhang, Xiangning; Liu, Shuming; Wang, Ziyou; Chen, Qicong; Wu, Yongfu; He, Zhiwei; Huang, Zunnan
Abstract : Respiratory syncytial virus (RSV) is the most frequent cause of hospitalization in infants worldwide. It is recognized by Toll‐like receptor 4 (TLR 4) and cluster of differentiation 14 (CD14) in the innate immune response. Previous case–control studies reported the influence of TLR4 Asp299Gly, TLR4 Thr399Ile, and CD14 C‐159T polymorphisms on the risk of severe RSV infection. However, a decisive conclusion has not been achieved. Therefore, we performed this meta‐analysis to examine the association between these three polymorphisms and the development of RSV bronchiolitis. A systematic literature search was performed using the PubMed, EMbase, Google Scholar Search, China National Knowledge Infrastructure, China Biological Medicine, and Wanfang Databases. The data were extracted and pooled odds ratios with 95% confidence intervals were calculated under six genetic models. A total of six studies with 1009 cases and 1348 controls, three studies with 473 cases and 481 controls, or four studies with 325 cases and 650 controls relating to each of the three polymorphisms were included in this meta‐analysis. The analyzed data indicated that all of these polymorphisms were not associated with the risk of severe RSV infection. This is the first meta‐analysis to investigate the relationship of TLR4 Asp299Gly, TLR4 Thr399Ile, and CD14 C‐159T polymorphisms with the risk of severe RSV infection. Although the results of this retrospective analysis indicated a lack of the association, more extensive multicentric studies with large sample sizes are necessary to provide a more reliable estimation of the association between these three polymorphisms and RSV bronchiolitis susceptibility.